Antimicrobial, Cytotoxic and Antioxidant Activities and Determination of the Total Tannin Content of Bark Extracts Endopleura uchi - Politi, Flavio A. S. [UNESP]; de Mello, Joao C. P.; Migliato, Ketylin F. [UNESP]; Nepomuceno, Andrea L. A. [UNESP]; Moreira, Raquel Regina Duarte [UNESP]; Pietro, Rosemeire C. L. R. [UNESP] (Mdpi Ag, 2011)
Endopleura uchi is a typical Amazonian tree and its bark is popularly employed in the preparation of teas against myomas, arthritis, influenza, diarrhea and cancer. In this study, the antioxidant activity, cytotoxicity and antimicrobial activity of five different extracts of the bark, selected by their total tannin content, were assessed. The potential antioxidant activity of the extracts was determined by 2.2-diphenyl-1-picrylhydrazyl radical scavenging assay and the values found were very similar among the extracts and to the standards antioxidants used in the tests. Cytotoxicity analysis in mammalian cells indicated that all the tested extracts exhibited IC(50) values higher than the highest concentration used, showing that they do not present a risk when consumed under these conditions. Extract tested against five bacterial strains and one yeast strain did not show satisfactory growth inhibitory activity, and even the extracts that showed some antimicrobial activity were not effective at any dilution to determine the minimum inhibitory concentration. The results may serve as a reference for subsequent works, since such reference values described in the literature for the bark of E. uchi.
Keywords: Endopleura uchi; minimum inhibitory concentration; IC(50); tannins